BODY, GIMNASTICS AND SEXUALITY IN THE HYGIENIC AND EUGENIC REFERENCE MANUALS IN CHILE 1870-1938 - Durán Sandoval, Manuel (Revista de Historia Social y de las Mentalidades, 2024)
This article tackles the conformation of a positive eugenic speech heir to the ambientalist/ environmentalist and racial hygienic theories of the late 19th century. This tendency strengthened between 1925 and 1938 through the conformation of an institutional structure and social programmes with strong positive eugenic shades, considering the body and the “character” of youth as the amalgam of the nation. In this context, from the late 19th century, attempts were developed to build a public medicine that would promote an education and youth preservation programme. This ambientalist/environmentalist initiatives pretended to enhance the young physical and moral skills through diets, hygiene and gymnastics.